Theranostic Calcium Phosphate Nanoparticles With Potential for Multimodal Imaging and Drug Delivery - Kalidoss, Madhumathi; Yunus Basha, Rubaiya; Doble, Mukesh; Sampath Kumar, T. S. (Frontiers in Bioengineering and Biotechnology, 2019)
Calcium phosphate (CaP) bioceramics closely resemble the natural human bone, which is a main reason for their popularity as bone substitutes. However, this compositional similarity makes it difficult to distinguish CaPs, especially in particulate form, from native bone by imaging modalities such as X-ray radiography, computed tomography (CT) and magnetic resonance imaging (MRI) to monitor the healing progress. External contrast agents can improve the imaging contrast of CaPs but can affect their physicochemical properties and can produce artifacts. In this work, we have attempted to improve the contrast of CaP nanoparticles via ion substitutions for multimodal imaging. Calcium deficient hydroxyapatite (CDHA) nanoparticles with silver (Ag), gadolinium (Gd) and iron (Fe) substitution were prepared by microwave accelerated wet chemical process to improve the contrast in CT, T1 (spin-lattice) and T2 (spin-spin) MRI relaxation modes respectively. Ag, Gd and Fe were substituted at 0.25, 0.5 and 0.25 at. % respectively. The ion substituted CDHA (ICDHA) were found to be phase pure by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR). Transmission electron microscopy (TEM) images showed that the ICDHA nanoparticles were platelet shaped and of (52±2) nm length and (6±1) nm width. The ICDHA showed high contrast in X-ray and CT compared to CDHA. The vibrating sample magnetometry (VSM) studies showed the ICDHA to exhibit paramagnetic behaviour compared to diamagnetic CDHA which was further confirmed by improved contrast in T1 and T2 MRI mode. In addition, the in vitro tetracycline drug loading and release was studied to investigate the capability of these nanoparticles for antibiotic drug delivery. It was found that a burst release profile was observed for 24 h with 47-52 % tetracycline drug release. The ICDHA nanoparticles also showed in vitro antibacterial activity against S.aureus and E.coli due to Ag, which was further enhanced by antibiotic loading. In vitro biocompatibility studies showed that the triple ion substituted ICDHA nanoparticles were cytocompatible. Thus, the ion substituted CDHA nanoparticles can have potential theranostic applications due to their multimodal image contrast, antibacterial activity and drug delivery potential. Future work will be conducted with actual bone samples in vitro or in animal models.